Organizational behavior managing people and organizations - Griffin, Ricky W.; Gully, Stanley Morris; Phillips, Jean 1969- (Cengage, 2020)
"Prepare to think and act like a manager with the powerful insights, solid concepts, and reader-friendly approach in Organizational behavior: managing people and organizations, 12th Edition. This text equips you with the skills and practical understanding to meet modern management challenges. You will delve into the fundamentals of employee behavior in today's organizations as the book balances classic management ideas with thorough coverage of the most recent organizational behavior developments and contemporary trends. Memorable examples from organizations and managers you will instantly recognize are woven throughout the book and work with new cases and boxed features that focus on pressing issues and reinforce the book's practical perspective. You'll also learn more about your strengths and areas where you need development though an array of self-assessment activities"--Publisher website.